Sejarah Peradaban Dinasti Umayyah Yang Membangun Jembatan Peradaban Islam - Abduh Al-Hafiedz; Dinda Safira tunisa; Umar Al-Faruq (Journal of Religion and Social Community | E-ISSN : 3064-0326, 2024)
This journal intends to provide an overview of the reign of Bani Umayyah (661-750 AD), an important period in the history of Islamic civilization marked by a significant change in the system of government, from consensus democracy to absolute monarchy. Supported by Muawiyah bin Abi Sufyan as the founder, the dynasty succeeded in expanding Islamic territory to North Africa, Spain and Central Asia, and achieved advances in education, art and architecture, as seen in the Umayyad Mosque in Damascus. Although the dynasty experienced its peak during the time of Umar bin Abdul Aziz, who was known as a just and reformist caliph, the Umayyads also faced various challenges, including social tensions, class differences, and rebellions, which ended its originality. This research uses the literature study method to analyze the contribution and impact of the Umayyad Dynasty in the formation and development of Islamic civilization, as well as its continuing influence in subsequent Islamic history